Synthesis and Electrochemical Characterization of Mesoporous MnO2 - Jia Chang Zhao; Jun Wang; Jing Li Xu (Journal of Chemistry)
The pore, crystal structure, and electrochemical performance of mesoporous MnO2 prepared by silica sol template method as electrode material for supercapacitor were investigated in this work. It is found that the crystal structure of nonporous and mesoporous MnO2 is confirmed to be β-MnO2 and the crystallinity of mesoporous MnO2 decreases due to the formation of mesopore. The results of electrochemical performance show that the specific capacitances of the sample prepared by using 20 g of Mn(NO3)2 solution and 40 g of silica sol (named MMO-4) at the scan rate of 5 mV/s are the highest (163.2 F/g), in comparison with 19.3 F/g of that of the sample of blank, suggesting the important role of pore-forming using silica sol as template. As the potential scan rate is raised to 200 mV/s, the specific capacitances of the sample of blank and MMO-4 are 12.2 F/g and 21.6 F/g, respectively. The great improvement of specific capacitance is probably due to the enlarged activated surface area after template is added.